Three-echelon supply chain inventory model for growing items. (3rd December 2019) - Sebatjane, Makoena; Adetunji, Olufemi
Abstract : Purpose: The purpose of this paper is to formulate a coordinated inventory control model for growing items in a supply chain with farming, processing and retail operations. The farmer grows newborn items and then delivers them to a processor once the items mature. At the processing plant, the items are slaughtered, cut and packaged at a specified rate. The processor then delivers a certain number of equally sized shipments of processed items to a retailer who satisfies customer demand. Design/methodology/approach: A cost minimisation inventory model describing the problem at hand is formulated with the number of shipments and the cycle time being the decision variables. A solution algorithm for solving the problem is presented and applied to a numerical example. Findings: Opting for an integrated policy is favourable to all supply chain members. When the proposed model is compared to equivalent independent and equal-cycle time replenishment policies, the total cost savings amount to 3 and 14 per cent, respectively. Social implications: The model can serve as a guideline for procurement managers dealing with growing items to better their inventory management practices. Considerable cost savings in food production chains can be achieved through improved inventory control, and these savings can be used to cushion consumers against rising food prices. Originality/value: Most previously published models on inventory management for growing items were formulated under the assumption that the items are grown and then sold to consumers instantaneously. In real food production systems, the items need to be transformed and packaged into a consumable form before customer demand is met. The model presented in this paper accounts for this and is therefore more realistic.